2008
DOI: 10.1021/bi702241t
|View full text |Cite
|
Sign up to set email alerts
|

Flash-Induced FTIR Difference Spectroscopy Shows No Evidence for the Structural Coupling of Bicarbonate to the Oxygen-Evolving Mn Cluster in Photosystem II

Abstract: Bicarbonate is known to be required for the maximum activity of photosystem II. Although it is well established that bicarbonate is bound to the nonheme iron to regulate the quinone reactions, the effect of bicarbonate on oxygen evolution is still controversial, and its binding site and exact physiological roles remain to be clarified. In this study, the structural coupling of bicarbonate to the oxygen-evolving center (OEC) was studied using Fourier transform infrared (FTIR) difference spectroscopy. Flash-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…Figure 6 demonstrates that injection of formate releases carbonate/hydrogencarbonate from the non-heme iron at the acceptor side of PSII (see also Govindjee et al 1991, 1997), while the destruction of the Mn 4 O x Ca cluster does not lead to a release of C i . This demonstrates the absence of a tightly bound C i within the water oxidizing complex (see also Ulas et al 2008; Aoyama et al 2008).
Fig.
…”
Section: Carbonic Anhydrasementioning
confidence: 80%
“…Figure 6 demonstrates that injection of formate releases carbonate/hydrogencarbonate from the non-heme iron at the acceptor side of PSII (see also Govindjee et al 1991, 1997), while the destruction of the Mn 4 O x Ca cluster does not lead to a release of C i . This demonstrates the absence of a tightly bound C i within the water oxidizing complex (see also Ulas et al 2008; Aoyama et al 2008).
Fig.
…”
Section: Carbonic Anhydrasementioning
confidence: 80%
“…The sample in the cell was separated from the vacuum (3 × 10 −8 bar) of the mass spectrometer via a 1-cm-diameter inlet that was covered by a 25-μm-thick silicon membrane (MEM-213; Mempro) resting on a porous Teflon support (Ø 10 mm). In the mass spectrometer the gases were ionized by electron impact and separated by a magnetic sector field into a seven-cup Faraday detector array for simultaneous detection of 16 (m/z 48). The simultaneous recording of argon (m/z 40) served as a control.…”
Section: Methodsmentioning
confidence: 99%
“…11 and 12). Although a tight binding of C i near the Mn 4 CaO 5 cluster is excluded on the basis of X-ray crystallography (3,14), FTIR spectroscopy (16), and mass spectrometry (17,18), the possibility that a weakly bound HCO − 3 affects the activity of PSII at the donor side remains a viable option (reviewed in refs. 10 and 19).…”
mentioning
confidence: 99%
“…Both approaches clearly demonstrated that the detected CO 2 /HCO − 3 does not originate from the inorganic core of the water-splitting site of PSII (Shevela et al, 2008a,b). Independent evidence for absence of HCO − 3 bound to the WOC was provided by FTIR and GS-MS experiments (Aoyama et al, 2008; Ulas et al, 2008). Moreover, in recent x-ray crystallography studies at resolutions of 1.9-3.0 Å no HCO − 3 was found in the vicinity of the Mn 4 CaO 5 cluster, while they all clearly show HCO − 3 bound to the NHI on the acceptor side of PSII (Guskov et al, 2010; Umena et al, 2011) (also, see Figure 1).…”
Section: Is Hydrogen Carbonate a Ligand To The Woc?mentioning
confidence: 96%